Efficient Hardware Trojan Detection with Differential Cascade Voltage Switch Logic. (11th May 2014) - Danesh, Wafi; Dofe, Jaya; Yu, Qiaoyan
Abstract : Offshore fabrication, assembling and packaging challenge chip security, as original chip designs may be tampered by malicious insertions, known as hardware Trojans (HTs). HT detection is imperative to guarantee the chip performance and safety. Existing HT detection methods have limited capability to detect small-scale HTs and are further challenged by the increased process variation. To increase HT detection sensitivity and reduce chip authorization time, we propose to exploit the inherent feature of differential cascade voltage switch logic (DCVSL) to detect HTs at runtime. In normal operation, a system implemented with DCVSL always produces complementary logic values in internal nets and final outputs. Noncomplementary values on inputs and internal nets in DCVSL systems potentially result in abnormal power behavior and even system failures. By examining special power characteristics of DCVSL systems upon HT insertion, we can detect HTs, even if the HT size is small. Simulation results show that the proposed method achieves up to 100% HT detection rate. The evaluation on ISCAS benchmark circuits shows that the proposed method obtains a HT detection rate in the range of 66% to 98%.